PENGARUH PENGGUNAAN METODE PEMBELAJARAN THE LEARNING CELL TERHADAP MOTIVASI BELAJAR PKN SISWA KELAS VIII SMP NEGERI 1 SINABOI SATU ATAP KABUPATEN ROKAN HILIR - Suraini Suraini '; Gimin Gimin '; Zahirman Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low students‟ motivation to learn civics at SMPN 1 Sinaboi District One Rokan Hilir. Formulation of the problem in this research was: How was the effectiveness of using the learning cell toward students„ motivation of PKn of VIII grade of SMPN 1 Sinaboi District One Atap Rokan Hilir? This study aims to determine the effectiveness of using the learning cell method toward students‟ motivation in learning civics of VIII grade students of SMP Negeri 1 Sinaboi One Atap Rokan Hilir. This research was conducted in SMP Negeri 1 Sinaboi District One on August until September 2015. This research was descriptive quantitative with population in this research was VIII grade students of SMP Negeri 1 Sinaboi District One Atap. The sample in this study were drawn based on the technique of "purposive sampling". Where classes which taken into the sample was class VIII B (experimental) where students given the method of learning cells, and class VIII C (control) students were given conventional method. Then the data analyzed by the homogeneity test and "t" test. Based on the results of the study, it indicated that there was significant effect using the learning cell method toward students' motivation between the experimental and control class in SMP Negeri 1 Sinaboi One Atap. (t = 23.79> table = 2.01). Where there was increase of average of students' motivation in learning civics in class experiment from 57.04 into 65.68 on the first meeting, on second meeting into 68.06, and 71, 96 on the third meeting. Then the average increase motivation to learn the control class of 54, 88 become 61.32 the first meeting, a second meeting 62.04 and 62.68 the third meeting. Thus the hypothesis which said that there was significant motivation in learning civics which use the learning cell method than using the conventional method at SMP Negeri 1 Sinaboi District One Atap Rokan Hilir.Keywords: Method of Learning the lerning cell, Motivation